The distribution kinetics of triiodothyronine: studies of euthyroid subjects with decreased plasma thyroxine-binding globulin and patients with Graves' disease - Cavalieri, Ralph R. (J Clin Invest, 1970)
The kinetics of distribution of 3,3′,5-triiodo-L-thyronine (T(3)) have been studied employing both a single-injection and a continuous infusion of T(3-)(131)I. External monitoring of radioactivity in the liver during the infusion permitted estimation of the hepatic distribution volume (V(H)) and the one-way hepatic clearance (C(H)) of the hormone. Among 10 euthyroid control subjects, V(H) averaged 2.07 liters ±0.50 (SD), and the mean value for C(H), 231 ml of plasma per min (±64). In three euthyroid men whose plasma showed decreased binding capacity by thyroxine-binding globulin (TBG) abnormally high V(H) and C(H) values were found, the increase in C(H) being proportional to the decrease in binding activity by plasma proteins. Among all 13 subjects, there was a high correlation (+ 0.86) between C(H) and the proportion of free hormone in plasma, measured in vitro. In four patients with hyperthyroid Graves' disease V(H) ranged from 3.2 to 4.2 liters and C(H) was elevated in every case, averaging 989 ml/min. The increase in C(H) in this group was out of proportion to the elevation of free hormone fraction in plasma. Seven patients who were either euthyroid or hypothyroid after treatment of Graves' disease showed a slight but significant increase in C(H) compared with the euthyroid controls without Graves' disease. The percentage of free hormone in the plasma of the treated group was normal or low and therefore could not explain the persistent elevation in unidirectional hepatic clearance observed. The rate of accumulation of labeled T(3) in the tissues of the thigh during the interval from 10 to 60 min of the sustaining infusion of tracer was slow compared to the rate of equilibration in the liver and did not differ significantly among the various groups studied. These latter findings suggest that in slowly equilibrating tissues such as the thigh the kinetics of T(3) distribution are relatively insensitive to alterations in hormone-binding activity by plasma proteins.